EKSPLORASI PEMBELAJARAN ORGANISASI MENGGUNAKAN FRAMEWORK 4I (INTUITING, INTERPRETING, INTERGRATING DAN INSTITUTIONALIZING) Studi Kasus pada UMKM Batik Tulis Lasem di Kabupaten Rembang - Syaiko Rosyidi; Sunarto Sunarto (BBM (Buletin Bisnis & Manajemen), 2019)
MSMEs have a significant role in the economy in Indonesia. Micro, Small and MediumEnterprises (MSMEs), is one of the leading driving forces in economic development (LPPI and BI,2015). In Indonesia itself, the existence of small industries is very important in saving the nationaleconomy. In Indonesia MSMEs have become an important part of the economic system. MSMEsare also able to create considerable employment opportunities for domestic workers, so it is veryhelpful in reducing the number of unemployed.This study aims to examine organizational learning with the 4I framework (intuiting,interpreting, integrating and institutionalizing) that is applied and carried out by Batik Tulis LasemMSMEs in Rembang District based on the business scale of small business groups and mediumbusiness groups. As well as examining the factors that become obstacles and driving the success oforganizational learning in Batik Tulis Lasem MSMEs in Rembang District.The results of the study show that: 1) The intuitive factors of individual SMEs in Batik aretriggered by their level of experience, and subjective perceptions that lead to leaps of success. 2)The learning of organizational interpreting from Lasem Batik Entrepreneurs is mostly obtainedfrom the feedback of interaction with stakeholders. 3) Integrating learning of the Batik Tulis LasemMSMEs organization that is more sharing among fellow batik entrepreneurs, enriching theirinsights and knowledge, so that it becomes an awareness and shared learning that with a solidcommunity (Cluster) Batik Tulis Lasem MSME can enhance mutual competitiveness. 4) Institalizingorganizational learning in the form of a joint commitment to maintain handmade batik that isloaded with designs that contain artistic and philosophical values as well as ancestral culturalreflections that have high economic values that are preserved in clusters and instill in generationsthat occur by individuals and groups in organizations that include systems, structures, procedures,and strategies with a framework of cultural wisdom and values.